2013
DOI: 10.1093/brain/awt035
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of Wilson’s disease in the United Kingdom

Abstract: Previous studies have failed to identify mutations in the Wilson's disease gene ATP7B in a significant number of clinically diagnosed cases. This has led to concerns about genetic heterogeneity for this condition but also suggested the presence of unusual mutational mechanisms. We now present our findings in 181 patients from the United Kingdom with clinically and biochemically confirmed Wilson's disease. A total of 116 different ATP7B mutations were detected, 32 of which are novel. The overall mutation detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
239
3
16

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(282 citation statements)
references
References 40 publications
7
239
3
16
Order By: Relevance
“…Sequencing of ATP7B in 1,000 control participants in the UK allowed the frequency of an individual carrying two mutant ATP7B alleles to be estimated at 1/7,026 (17). The most common mutation in Europe and North America is p.H1069Q (1).…”
Section: Wd In Western Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of ATP7B in 1,000 control participants in the UK allowed the frequency of an individual carrying two mutant ATP7B alleles to be estimated at 1/7,026 (17). The most common mutation in Europe and North America is p.H1069Q (1).…”
Section: Wd In Western Countriesmentioning
confidence: 99%
“…The prevalence of WD is higher in China than in the West (18). Since the first estimate of WD in 1968, considerable progress has been made in China.…”
Section: Wd In Asiamentioning
confidence: 99%
“…WD is an eminently treatable monogenic disease [5]. Its main symptoms include hepatic and neurological disorders ranging from mild abnormities to aggravated progressions [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…3,000 in East Asia and 1: 7,000 in the United Kingdom [3][4][5]. Typical features of WD include hepatic dysfunction, neurological disorders, psychiatric symptoms, corneal Kayser-Fleischer (K-F) rings, and low serum ceruloplasmin levels [6][7][8].…”
mentioning
confidence: 99%
“…Clinical prevalence of diagnosed WD is~30 per million population, but this is probably an inaccurate estimate as a recent genetic study reported the frequency of individuals predicted to carry two mutant pathogenic ATP7B alleles to be 1/7026 [9].…”
Section: Wilson's Disease (Wd)mentioning
confidence: 99%